18-Fluorodeoxyglucose positron emission tomography/computed tomography for assessment of response to brentuximab vedotin treatment in relapsed and refractory Hodgkin lymphoma. Issue 4 (April 2014) - Kahraman, Deniz; Theurich, Sebastian; Rothe, Achim; Kuhnert, Georg; Sasse, Stephanie; Scheid, Christoph; Dietlein, Markus; Drzezga, Alexander; von Bergwelt-Baildon, Michael; Kobe, Carsten
Abstract Brentuximab vedotin has emerged as a possible treatment option in patients suffering from relapsed and refractory Hodgkin lymphoma (HL). We investigated the role of 18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) for monitoring treatment response to brentuximab vedotin in patients with relapsed and refractory HL. Twelve consecutive, heavily pretreated patients with relapsed and refractory HL treated with brentuximab vedotin were available for analysis. FDG-PET/CT studies were performed early during treatment after a median of 3 cycles (range, 2–5 cycles), and were analyzed visually using a 5-point scale (5PS) and quantitatively using the maximum standardized uptake value (SUVmax) and the three-dimensional (3D) isocontour at 50% of the maximum pixel value (SUV50) in the hottest single lesion. The median follow-up in our study cohort was 16 months (range, 5–30 months). The median progression-free survival (PFS) was 12.5 months and PFS at 12 months was 58%. Patients treated with brentuximab vedotin and negative interim FDG-PET/CT assessed by visual or quantitative analysis demonstrated a significantly prolonged PFS compared to patients with positive interim FDG-PET/CT. The 1-year PFS was 100% in patients with negative interim FDG-PET/CT assessed by visual analysis, whereas patients with positive interim FDG-PET/CT had a worse outcome with a 1-year PFS of 38% (p = 0.033). The 1-year PFS was 75% in patients with negative interim FDG-PET/CT assessed by quantitative analysis using the SUV50, whereas patients with positive interim FDG-PET/CT had a worse outcome with a 1-year PFS of 25% (p = 0.017) Interim FDG-PET/CT might be a suitable diagnostic approach to predict response to brentuximab vedotin in relapsed and refractory HL.